2013
DOI: 10.1007/978-1-4614-7411-1_32
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Metabolic Evaluation of Breast Tumor Mouse Xenografts for Predicting Aggressiveness Using the Hyperpolarized 13C-NMR Technique

Abstract: In vivo imaging/spectroscopic biomarkers for solid tumor aggressiveness are needed in the clinic to facilitate cancer diagnosis and treatment strategies. In mouse models of human melanoma and breast cancer we were able to detect the metabolic differences among tumors of different metastatic potential and between normal and cancer tissues by optical imaging of the mitochondrial redox state of snap-frozen tissue samples. Such metabolic differences indicate that tumors of different aggressiveness have different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…All NMR experiments were performed with a 1.1-cm or 1.4-cm 1 H/ 13 C dual-tuned home-made surface coil in a 9.4-T Varian vertical bore NMR spectrometer as previously described (32, 33). The tumor-bearing mice were anesthetized by administering oxygen doped with 1% isofluorane while the body temperature was maintained at ~35.0±2.5 °C with heated air.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All NMR experiments were performed with a 1.1-cm or 1.4-cm 1 H/ 13 C dual-tuned home-made surface coil in a 9.4-T Varian vertical bore NMR spectrometer as previously described (32, 33). The tumor-bearing mice were anesthetized by administering oxygen doped with 1% isofluorane while the body temperature was maintained at ~35.0±2.5 °C with heated air.…”
Section: Methodsmentioning
confidence: 99%
“…the reaction rate constants of the lactate dehydrogenase-catalyzed reaction as described by Li et al (32, 33). The principles of the analysis are briefly summarized as follows.…”
Section: Methodsmentioning
confidence: 99%
“…13 C MRI. HP [1-13 C] pyruvate has been used to test the degree of aerobic glycolysis versus tumor progression in breast cancer cell xenografts in mice, with higher conversion rates observed for more indolent xenografts (Xu et al 2013(Xu et al , 2014. Several studies have also looked at biologic factors modulating the observed metabolic signals in breast cancer studies, including perfusion (Lau et al 2016c), cellular transport (Harris et al 2009), and endogenous lactate and lactate dehydrogenase (LDH) concentrations (Lodi et al 2013).…”
Section: Diffusion Weighted Imaging (Dwi)mentioning
confidence: 99%
“…Hyperpolarized 13 C MRS/MRSI has specific applications in breast cancer but with sometimes unexpected results. For example, Xu et al explored differences in the apparent conversion rate of pyruvate-to-lactate (k PL ) in mouse xenograft models of breast cancer with different levels of aggressiveness and found that more indolent tumors exhibited higher k PL values, contrary to the conventional model of upregulated aerobic glycolysis predicted by the Warburg hypothesis [ 9 , 10 ]. In contrast, Ward et al demonstrated the sensitivity of hyperpolarized pyruvate-to-lactate conversion to LDH modulation by inhibiting phosphoinositide 3-kinases (PI3K), a key enzyme implicated in cancer development and involved in regulating LDH concentrations [ 11 ].…”
Section: Introductionmentioning
confidence: 99%